THE CHOICE OF LANGUAGE BY ELEMENTARY STUDENTS IN LANGSA - Angga Fitra Jaya 010395150403013 (Universitas Samudra, 2020)
The purpose of this research are: To find out how processelementary students in SDN 14 langsa choosing languagein the telling story through picture and their parents to find out what factors that influencing their language choice. This research uses descriptive qualitative methods, namely observation, semi-structured interviews and documentation. The subjects of this research are twenty students and twenty parents in Langsa. The research instruments were picture, questions, recording equipment and documentation. The procedure for collecting data is library research, conducting interviews, voice recorders and concluding. The result of this research are elementary students in SDN 14 Langsa mostly choosing indonesia language in telling the story in front of the class in otherway same as their parents opportunities in the environment. And factors that influence the use of the term language choice in elementary students are theirparents language use in social status practice.